Sustainable Palm Oil: Dissecting a Global Debate - Noordwijk, M. van (IOP Publishing, 2020)
Palm oil expansion in tropical forest margins captures headlines, primarily out of concern that encroachment to tropical forest causes environmental problem and ignites social issues [1]. Sustainability has to be understood in the wider context of the 17 Sustainable Development Goals (SDGs), rather than as primarily a plot-level ecological concern about persistence of production, to make sense of the debate that has become a very polarized and find ways forward. Cascading ecological and social issues have caused a loss of trust, (threats of) consumer boycotts and multiple standards and certification responses. Diverse sustainability issues have come up as part of a public issue-attention cycle with five recognisable stages [2]: A) Agenda setting, B) Better and widely shared understanding of what is at stake, C) Commitment to common principles, D) Details of devils derailing operations, devolved to (newly created or existing) formal institutions that handle implementation and associated budgets, and E) Efforts to monitor and evaluate effects. In Indonesia two phases of new establishment of palm oil coexist within a forest transition gradient: (i) (industry-led) expansion into new forest margins with many social and ecological consequences; and (ii) (often farmer-led) conversion of existing agroforestry and tree crop (often rubber-based) or pasture economies in mosaic landscapes. External consumer concerns refer to the expansion phase, rather than to production sustainability or issues of smallholder concern. However, certification standards are only partially adjusted to the latter. After a 'voluntary industry standards' phase of differentiation with and shifting blame to non-certified others [3], government involvement in Malaysia and Indonesia suggests that standards and certification can trickle down to enforceable good practice standards for all. This can learn from past ineffective policies that did not address the real issues in local context [4]. On the other hand, subnational jurisdictional entities are the scale at which oil palm production can be balanced with other goals, such as forest conservation and smallholder welfare. This needs a supportive and clear national policy support that combines clarity on forest protection (as in the now permanent moratorium), with support for risk-reducing diversified smallholder oil palm production systems [5,6] and international communication that acknowledges past problems but shows Indonesia is ready to move on, connecting all the dots of sustainable development goals.